Elimination of Schistosoma japonica in Central Sulawesi, Indonesia Intermediate Snail Control and Utilization Medicinal Plants - Charisma, Acivrida Mega; Naftalia, Anjelline; Ramadhan, Alfian Anwar Putra; Aulia, Rasyida Salma; Solikhah, Ferdina Amalia; Muasyaroh, Husnul; Maslakha, Vina Lailatul; Hikmah, Nurul; Belina, Ken Dyah Ayu; Adinda, Hilda; Wulandari, Siska (Journal of Parasite Science, 2025)
Schistosomiasis is a zoonotic health problem caused by infection with the schistosoma class parasite, which lives in human blood vessels and around the intestines and bladder. Intermediate hosts in the form of snails and definitive hosts in animals and humans can be influenced by physical, chemical and biological environmental conditions. Schistosomiasis in Indonesia is caused by the trematode worm Schistosoma japonica (S. japonicum) with the intermediate host being the snail Oncomelania hupensis lindoensis. Schistosomiasis is still a public health problem in endemic areas. In Indonesia, schistosomiasis is only found in Central Sulawesi Province, namely the Napu Plateau and Bada Plateau, Poso Regency and Lindu Plateau, Sigi Regency. S. japonica is currently endemic in three very remote areas in Central Sulawesi Province, Indonesia. An integrated schistosomiasis control program has been implemented, however, the reported prevalence data shows a trend of increasing schistosomiasis prevalence in three endemic areas in Central Sulawesi. Eliminating schistosomiasis in Indonesia is not easy. This review will examine several challenges hindering the implementation and sustainability of schistosomiasis elimination programs, including the S. japonica intermediate snail control program and the use of medicinal plants for the treatment of schistosomiasis.